2015
DOI: 10.1097/fjc.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-204 Targets Runx2 to Attenuate BMP-2-induced Osteoblast Differentiation of Human Aortic Valve Interstitial Cells

Abstract: Osteoblast differentiation of valve interstitial cells (VICs) is a key step in valve calcification, but the molecular mechanisms involved are not fully understood. In this study, we aimed to investigate whether microRNA (miR)-204-regulated VICs differentiation through modulation of runt-related transcription factor 2 (Runx2), a key transcription factor for osteogenesis. Our data demonstrated that miR-204 was markedly downregulated in both human calcified aortic valves and bone morphogenetic protein (BMP)-2-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…Modifications of miR-125b-5p level have been involved in arterial calcification by smooth muscle cells 37 by regulating their transdifferentiation into osteoblast-like cells through the regulation of SP7 and RUNX2, 36 a marker of osteogenesis also found to be involved in arterial calcification. 38,39 MiR-204-5p also directly targets RUNX2. Five other target genes were found to be common between both miRNAs, including HAPLN1, an extracellular matrix protein interacting with proteoglycans and involved in cartilage development.…”
Section: Discussionmentioning
confidence: 98%
“…Modifications of miR-125b-5p level have been involved in arterial calcification by smooth muscle cells 37 by regulating their transdifferentiation into osteoblast-like cells through the regulation of SP7 and RUNX2, 36 a marker of osteogenesis also found to be involved in arterial calcification. 38,39 MiR-204-5p also directly targets RUNX2. Five other target genes were found to be common between both miRNAs, including HAPLN1, an extracellular matrix protein interacting with proteoglycans and involved in cartilage development.…”
Section: Discussionmentioning
confidence: 98%
“…Using the broad parameters “aortic | valve”, Abcam Firefly Discovery Engine identified 30 publications on 41 miRNAs related to various biological processes, including fibrosis ( miR-21 [62]), inflammation ( miR-125b [63]; miR-148a [64]), differentiation ( miR-204 [65]), and calcification ( miR-141 [66]; miR-204 [65]; miR-30b [67]; miR-214 [68]). Tables 1 and 2 provide an overview of the profiling and functional studies that have been conducted to highlight the roles of these miRNAs in their respective target pathways.…”
Section: Mirna In Aortic Valve Diseasementioning
confidence: 99%
“…Multiple studies demonstrated that miR-30b is functionally involved in the prevention of osteogenesis and apoptosis by direct targeting of Runx2, Smad1, and caspase-3 [67,69]. Similarly, miR-26a down-regulates multiple genes related to calcification [69], miR-141 blocks TGF- β -triggered BMP-2 signaling, and miR-204 represses Runx2 [66], consequently inhibiting osteogenic differentiation [65]. Thus, valve calcification could be caused by negative regulation of these miRs, which would abrogate various protective mechanisms.…”
Section: Mirna In Aortic Valve Diseasementioning
confidence: 99%
“…An in vivo experiment also showed that miR-138 negatively regulates osteoblast differentiation and bone formation [20]. Other miRNAs, such as miRNA-194, miRNA-210, miRNA-204, miRNA-24, miRNA-23, miRNA-145, miRNA-375, and miRNA-150, have also been confirmed to participate in this process [2126]. Zhou et al showed that miR-17-92 cluster critically regulates bone metabolism, mostly through its function in osteoblasts [27].…”
Section: Role Of Osx and Mirnas In Osteoblastsmentioning
confidence: 99%